Implementasi Metode Operational Competitiveness Rating Analysis (OCRA) Dengan Pembobotan Rank Order Centroid (ROC) Dalam Pengambilan Keputusan Penilaian Supir Barang Terbaik - Iqbal, Muhammad (CV. Graha Mitra Edukasi, 2023)
An assessment of a position is very important for a company in order to improve good performance. One of them is a goods driver, some of the duties of a goods driver at CV.Solusi are to maintain the safety and condition of the goods to be sent. The assessment of the best goods drivers is a form of assessment of the quality and quantity produced by the drivers. The problem faced by CV.Solution in assessing the best goods drivers is the lack of transparency and only relying on the memory of the party making the decision. Based on the problems that have been described, the process of assessing the best goods driver requires a Decision Support System (DSS) which can assist in making more effective decisions regarding the assessment of the best goods driver. Building a SPK using the OCRA method and ROC weighting in creating a system can make it easier for users to do this. The results of this research show that there is a Decision Support System (DSS) with the implementation of the OCRA and ROC methods, the assessment carried out by CV.Solusi produces focused and directed decisions so that the decision results are effective and efficient.